THE INTERSECTION OF DISABILITY AND MENTAL HEALTH: UNDERSTANDING THE COMPLEXITIES - Ahmed, Naseem; Khan, Sadaf; Beg, Mirza Juned (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rights of person with mental disabilities are a significant issue which is being faced today, and there is an evident connection between mental health and human rights. However, it is concerning that the topic of mental disability has received little attention in literature on public health and human rights. There are many people with mental disabilities, which account for a large percentage of disability. There is a huge social and financial burden associated with mental disability that is carried by people, families, communities, and countries. Kenneth Bums has demonstrated the well-established link between mental disorders and homelessness, social exclusion and alienation, poverty, and financial disparity. Mental illness has an effect on social behaviour, education, economic output, and cultural standards. The social, environmental, and economic context in which a person is born, grows, works, and ages shapes that person’s mental health.